A case control study on relationship of colorectal cancer and smoking exposure in Hospital Universiti Sains Malaysia - Euxian, Lee (2014)
Background: There have been inconsistent findings in the association between colorectal cancer and smoking exposure. Most reported data were from western population groups with only few involving Asian population while there’re no available local data from Malaysia. As the causes of colorectal cancer are multifactorial, the genetic susceptibility, lifestyle and diet difference between Western and Asian population may be important in determining the overall individual risks across the world. Methods: This study investigates such association in our local population at Hospital Universiti Sains Malaysia in Kelantan. Our case-control study involves patients diagnosed with colorectal cancer from 2005 till 2011 which is matched to a group of controls without the tumour. Data were collected from the patients file records and supplemented further by phone interviews or clinic follow up to complete the validated study proforma. We included a total of 92 cases matched with 92 controls. Results: Current regular smokers have an overall significant association and increased risk of developing CRC (OR = 2.26: CI 95% 0.90-5.89). Increasing number of cigarettes smoked per day is related towards higher rectal cancer risk as compared to colon cancer (p value 0.009). There’s statistically no significant association between dose-duration of cigarette smoking and the CRC risk however we find those who smoked over 30 years and had more than 20 cigarettes / day had higher OR of 1.92 compared to 1.42 of developing CRC in non-smokers. The cessation of smoking for 30 years could eventually reduce the OR to 1.13 closer to the baseline of non-smokers however again the data is statistically non significant. Conclusion: We report a positive association of CRC risk in current smokers among our local population at Hospital Universiti Sains Malaysia in Kelantan with heavy smokers having a higher incidence of rectal cancer. The link between smoking and CRC is important in view of the high incidence of CRC in our country and the ever increasing number of smokers and in view of smoking as a modifiable risk. These findings may be use in educating the public on smoking cessation and also helping healthcare providers in screening patients in the high risk group for early detection of CRC. It also provides us with more local data on which is still very few and a role in future studies. Keywords: Cigarette smoking, colorectal cancer, case-control study.